2010
DOI: 10.1111/j.1539-6975.2010.01396.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Insurance Help to Escape the Poverty Trap?—A Ruin Theoretic Approach

Abstract: Poverty trapping refers to the fact that poor people in developing countries cannot escape their poverty without help from outside. This is worsened by extreme events, for example, floods or hurricanes, sending people to poverty who have not been poor before. Often, insurance is seen as a way out. This article studies poverty trapping in the context of catastrophic risk and introduces a ruin-type model, combining deterministic growth with a stochastic loss model. We analyze the properties of the resulting piec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Indeed, no homeowner would prefer to stay uninsured against earthquake risk if the annual average premium were to decrease from USD 980 (as observed in 2016) to USD 160 (USD 2015) or lower. Moreover, Kovacevic and Pflug (2011) have shown that a minimum capital is required to benefit from an earthquake insurance cover, otherwise the cost of the premium would be more than the potential risk. They have also found that the lower the insurance premium, the lower this minimum capital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, no homeowner would prefer to stay uninsured against earthquake risk if the annual average premium were to decrease from USD 980 (as observed in 2016) to USD 160 (USD 2015) or lower. Moreover, Kovacevic and Pflug (2011) have shown that a minimum capital is required to benefit from an earthquake insurance cover, otherwise the cost of the premium would be more than the potential risk. They have also found that the lower the insurance premium, the lower this minimum capital.…”
Section: Discussionmentioning
confidence: 99%
“…They have also found that the lower the insurance premium, the lower this minimum capital. Consequently, the results of Kovacevic and Pflug (2011) suggest that some uninsured people can be well aware of the earthquake risk but just cannot afford earthquake insurance at the current price. This corroborates the result of the present study because bringing such people to buy earthquake insurance is foremost a matter of price, not of insufficient risk perception.…”
Section: Discussionmentioning
confidence: 99%
“…As the opportunity costs are mostly food and livelihood related this is an important issue to be considered in the future. It was already stated in the literature (see Barret et al 2007;Pflug et al 2011) that different initial wealth levels (or asset levels) will demand different risk management strategies. That being said, it may be the case that for the poorest of the poor, subsidies have to be granted as well as technical assistance (see Linnerooth-Bayer et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The growth-fragmentation process that we consider has been introduced by Kovacevic and Pflug [2011] for modeling a capital subject to random heavy loss events. We do not attempt to give an exhaustive survey about this model, but refer the reader to the paper [Kovacevic and Pflug, 2011] and the references therein. We consider an individual household whose income I t at time t may be split into…”
Section: A Ruin Theoretical Modelmentioning
confidence: 99%
“…This stochastic process has already been introduced by Kovacevic and Pflug [2011] as a theoretical model for insurance, for which Γ is called area of poverty. Kovacevic and Pflug [2011] establish that the ruin probability p(x) is the solution of an integral equation that they solve numerically. In many aspects, our work and the aforementioned paper are different and complementary.…”
Section: Introductionmentioning
confidence: 99%